Improving KPK and FPB Concepts Through Interactive TTS Media - Eva Fitriana; Indah Setyaningsih; Mujiono (Schola, 2025)
ABSTRACT This study aims to improve the understanding of fifth grade students of Lobang 02 Elementary School regarding the concept of Least Common Multiple (LCM) and Greatest Common Factor (GCF) by using interactive media in the form of crossword puzzles (TTS). This study is included in the Classroom Action Research (CAR) type which is carried out in two cycles. The research subjects consisted of 16 students. Data collection tools used include learning outcome tests, observation sheets, and student response questionnaires. From the results of the study, there is an increase in student learning outcomes from the first cycle to the second cycle. In the pre-action stage, only 31.25% of students achieved learning mastery with an average score of 61.2. After the action was carried out in the first cycle, mastery increased to 56.25% with an average score of 72.8. In the second cycle, learning mastery reached 87.5% with an average score of 84.5. This increase shows that the TTS media is effective in helping students understand the concepts of LCM and GCF and creating a more active and enjoyable learning atmosphere. In conclusion, interactive media in the form of crossword puzzles can be an alternative learning strategy that can improve students' mathematics learning outcomes in elementary schools.